Circulating complement component 4d (C4d) correlates with tumor volume, chemotherapeutic response and survival in patients with malignant pleural mesothelioma. Issue 1 (December 2017) - Klikovits, Thomas; Stockhammer, Paul; Laszlo, Viktoria; Dong, Yawen; Hoda, Mir; Ghanim, Bahil; Opitz, Isabelle; Frauenfelder, Thomas; Nguyen-Kim, Thi; Weder, Walter; Berger, Walter; Grusch, Michael; et al.
Abstract Only limited information is available on the role of complement activation in malignant pleural mesothelioma (MPM). Thus, we investigated the circulating and tissue levels of the complement component 4d (C4d) in MPM. Plasma samples from 55 MPM patients, 21 healthy volunteers (HV) and 14 patients with non-malignant pleural diseases (NMPD) were measured by ELISA for C4d levels. Tissue specimens from 32 patients were analyzed by C4d immunohistochemistry. Tumor volumetry was measured in 20 patients. We found no C4d labeling on tumor cells, but on ectopic lymphoid structures within the tumor stroma. Plasma C4d levels did not significantly differ between MPM, HV or NMPD. Late-stage MPM patients had higher plasma C4d levels compared to early-stage (p = 0.079). High circulating C4d was associated with a higher tumor volume (p = 0.047). Plasma C4d levels following induction chemotherapy were significantly higher in patients with stable/progressive disease compared to those with partial/major response (p = 0.005). Strikingly, patients with low C4d levels at diagnosis had a significantly better overall survival, confirmed in a multivariate cox regression model (hazard ratio 0.263, p = 0.01). Our findings suggest that circulating plasma C4d is a promising new prognostic biomarker in patients with MPM and, moreover, helps to select patients for surgery following induction chemotherapy.